Serializability Improves Parallel Execution of Production System - Amaral, José Nelson; Ghosh, Joydeep (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1995: Anais do VII Simpósio Brasileiro de Arquitetura de Computadores e Processamento de Alto DesempenhoDO - 10.5753/sbac-pad.1995.19861, 1995)
This paper presents a new production system architecture that uses serializability as a correctness criterion to select a set of productions to be executed in parallel. The use of serializability eliminales global synchronization. This architecture takes advantage of modern associative memory devices to allow parallel production firing, concurrent matching, and overlap among matching, selection, and firing of productions. A comprehensive event driven simulator is used to evaluate the scaling properties of the new architecture and to compare it with a parallel architecture using global synchronization before every production firing. Our results indicate that the combination of serializability and associative memories can achieve substantial improvements in speed with a very modest increase in hardware cost.